STUDIES ON CALVES SALMONELLOSIS 1. INCIDENCE OF SALMONELLA SEROTYPE IN CALVES - A. Yass, A.; S. Barhoom, S.; F. Al-Juboori, S. (The Iraqi Journal of Veterinary Medicine, 1990)
With a view to determine the prevalence of salmonellosis in calves in Baghdad, a systematic survey was conducted, involving calves herds located in two different regions of Baghdad. This study, though limited, revealed that the overall incidence of salmonellosis was 29.01 % (33.33 % in white Gold herd and 24.30% in AL-Futhalia herd). This study also revealed that out of 57 isocates, 14 different serotype was obtained. Of these, S. dublin and S. typhimurium were the commonest serotype isolated from calves (26.32% and 17.54 %respectively).